Job Stress of Tourism Industry Employees Due to Covid-19: A Systematic Literature Review - Priyanto, Rahmat (Media Wisata, 2023)
The tourism industry has been badly affected by the Covid 19 pandemic. The policy of limiting tourism travel activities has led to uncertainty in the tourism business. Besides, tourism industry workers are at high risk of contracting the Covid 19 virus because tourism services must be done directly with tourists. Many workers in the tourism industry experience work stress due to the Covid 19 pandemic. This systematic literature review study examines tourism worker stress due to the Covid 9 pandemic. The literature review method uses a cross-sectional search of health, tourism, and management articles. The search results were eight articles selected by Prisma Chart with defined inclusion and exclusion criteria. The results of a systematic literature review study revealed that the perceived threat of the Covid 19 virus causes fear and worry about being infected. Another factor that causes stress for tourism workers regarding job insecurity is perceived uncertain job continuity. Experienced work stress has an impact on decreasing job satisfaction and well-being, then can increase the turnover intention of workers from the company. Several strategies can be implemented to reduce work stress by providing self-protection tools, service rules, adjusting work assignments, and preparing transformational leadership to increase the company's resilience in facing various external conditions.